Phase-field simulation of grain nucleation, growth, and Rayleigh distribution of U3Si2 nuclear fuel - Ma, Cong; Zhao, Min; Xin, Tianyuan; Wu, Lu; Pan, Rongjian; Qin, Jiantao; Zhang, Jing (Frontiers in Energy Research, 2023)
U3Si2 is a potential accident-tolerant fuel (ATF) due to its high thermal conductivity and uranium density relative to UO2. The grain size and distribution play an essential role in the service performance of U3Si2. However, the grain evolution is quite complicated and remains unclear, which limits further application of U3Si2 in the ATF assembly. In the present work, a phase-field model is employed to investigate the nucleation and growth of grains in U3Si2. Our results show that the number of grains rises rapidly at the nucleation stage until they occupy the whole system. After that, the grain radius and area continue to grow, and the grain number decays. The grain area increases in time according to the linear law, while the mean grain radius increases with time in a power law form with the scaling growth exponent z = 0.42, which is quite close to the theoretically predicted value. Finally, we performed statistical analysis and found that the grain size evolution of U3Si2 obeys Rayleigh distribution. Our simulation not only elucidates the nucleation and evolution of grains in U3Si2 during the thermal treatment process unambiguously but also provides a fundamental study on the investigation of grain growth, subdivision, and even amorphization in the irradiated condition, which is very important for U3Si2 used as ATF in the light water reactor.